2016
DOI: 10.1002/cnm.2782
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of brain tissue responses because of the underwash overpressure of helmet and faceshield under blast loading

Abstract: Head protective tools such as helmets and faceshields can induce a localized high pressure region on the skull because of the underwash of the blast waves. Whether this underwash overpressure can affect the brain tissue response is still unknown. Accordingly, a computational approach was taken to confirm the incidence of underwash with regards to blast direction, as well as examine the influence of this effect on the mechanical responses of the brain. The variation of intracranial pressure (ICP) as one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…They also showed that the underwash overpressure occurred at the opposite side of the incoming waves in front and back directions. Moreover, in another study on the effects of underwash on the brain tissue response, they studied the same blast directions used here using a FEA approach and found similar results in terms of the location and intensity of the underwash overpressure (Sarvghad-Moghaddam et al 2016). The dependence of the underwash on the direction of the blast was also among their results.…”
Section: Disclosure Statementsupporting
confidence: 62%
See 2 more Smart Citations
“…They also showed that the underwash overpressure occurred at the opposite side of the incoming waves in front and back directions. Moreover, in another study on the effects of underwash on the brain tissue response, they studied the same blast directions used here using a FEA approach and found similar results in terms of the location and intensity of the underwash overpressure (Sarvghad-Moghaddam et al 2016). The dependence of the underwash on the direction of the blast was also among their results.…”
Section: Disclosure Statementsupporting
confidence: 62%
“…This phenomenon may also affect the performance of these tools under blast compared to their high efficiency under impact (SarvghadMoghaddam et al 2015). Sarvghad-Moghaddam et al (2016) showed that underwash-induced overpressure on the head has the potential of imposing higher risk of brain injury. While parameters such as the blast intensity and direction, as well as the shockwave flow mechanics can affect underwash, the underlying cause for underwash is still a question.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental methods impose moral and technical issues before conducting any research. Many FE studies have been conducted to determine brain responses under dynamic loads to study TBIs [1][2][3][4][5][6][7][8][9][10]. Such studies have helped to e ciently develop TBI prediction tools based 1 on the current injury threshold criteria of kinematics, intracranial pressure (ICP), tissue strain, and tissue shear stress [11].…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have helped to e ciently develop TBI prediction tools based 1 on the current injury threshold criteria of kinematics, intracranial pressure (ICP), tissue strain, and tissue shear stress [11]. Mechanical responses of human head brain and skull have been studied using multi-material FE simulations [5,12]. Representative FE head models, which include major components of the head such as brain, skull bones, and cerebrospinal uid (CSF), have been employed to study the response of the head under di erent loadings.…”
Section: Introductionmentioning
confidence: 99%